Mitochondrial Quality Control in Hepatocellular Carcinoma - Bian, Jinda; Zhang, Dan; Wang, Yicun; Qin, Hanjiao; Yang, Wei; Cui, Ranji; Sheng, Jiyao (Frontiers in Oncology, 2021)
Mitochondria participate in the progression of hepatocellular carcinoma (HCC) by modifying processes including but not limited to redox homeostasis, metabolism, and the cell death pathway. These processes depend on the health status of the mitochondria. Quality control processes in mitochondria can repair or eliminate “unhealthy mitochondria” at the molecular, organelle, or cellular level and form an efficient integrated network that plays an important role in HCC tumorigenesis, patient survival, and tumor progression. Here, we review the influence of mitochondria on the biological behavior of HCC. Based on this information, we further highlight the need for determining the role and mechanism of interaction between different levels of mitochondrial quality control in regulating HCC occurrence and progression as well as resistance development. This information may lead to the development of precision medicine approaches against targets involved in various mitochondrial quality control-related pathways.